Aloe Vera aqueous extract and yogurt enhance peripheral immune cells, and brain astrocytes response in rats. - Alzhraa Hefny; Mahmoud Awad; Mohammed Youssef (SVU-International Journal of Veterinary Sciences, 2023)
Aloe Vera (AV) is a reputable herbal medical and feed additive. The gel extract of AV contains mucopolysaccharides that stimulate the innate immune response. The reaction to Aloe Vera administration might involve beneficial or drastic responses depending on the dose and extraction method. In the current investigation, two different concentrations of Aloe Vera gel extract at 10% and 20% were orally administrated for one week either alone or as a supplement to yogurt. Wistar albino rats were randomly distributed into6 groups and administered orally : 1 Distilled water (DW) group, 2) Aloe Vera gel extract 10% (AV10) group, 3) Aloe Vera gel extract 20% (AV20) group, 4) Plain yogurt group (Y), 5) Aloe Vera 10% fortified yogurt group (Y + AV10), and 6) Aloe Vera 20% fortified yogurt (Y + AV20) group . The effects of different treatments were investigated on body weight, feed intake, the proliferation of brain astrocytes, differential count of peripheral immune cells, and serum proteins. AV20 neutrophilia with a lymphocytopenia. Glial fibrillary acidic protein (GFAP), a marker of astrocytes, was significantly enhanced in brain tissues that received Aloe Vera-fortified yogurt with nonsignificant enhancement in other groups. No prominent changes were observed in serum proteins and antioxidant activity. In conclusion, Aloe Vera could enhance the proliferation of brain astrocytes and innate peripheral immune cells without further changes in proteins and antioxidant activity and the response of astrocytes to Aloe Vera in the brain is augmented by yogurt.